2023
DOI: 10.1002/jbio.202300039
|View full text |Cite
|
Sign up to set email alerts
|

Macular choroidal thickness and correlations in a healthy pediatric South Asian cohort: A spectral domain optical coherence tomography study

Abstract: The objective of this study is to assess the normative macular choroidal thickness (ChT) in healthy children with spectral domain optical coherence tomography (SD-OCT) and study its correlations with age, intraocular pressure, axial length, corneal thickness, cup-to-disc ratio, and spherical equivalent. Methods: This study recruited 89 healthy children. Macular ChT was measured in five locations, subfoveal, 1500 μm and 3000 μm nasal, and temporal to the fovea via the Optopol REVO80 ® SD-OCT. Results: The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(77 reference statements)
0
0
2
Order By: Relevance
“…On the other hand, in a wide-field study, Hirano et al found a weak negative correlation for selected sectors of the choroid. Nadeem did not find such a correlation in a large group of children [22]. Our analysis differs from most previous studies as it applied both multifactor statistic modeling (age and gender adjustment) and wide-field OCT testing.…”
Section: Axial Length and The Rt And Ctcontrasting
confidence: 68%
“…On the other hand, in a wide-field study, Hirano et al found a weak negative correlation for selected sectors of the choroid. Nadeem did not find such a correlation in a large group of children [22]. Our analysis differs from most previous studies as it applied both multifactor statistic modeling (age and gender adjustment) and wide-field OCT testing.…”
Section: Axial Length and The Rt And Ctcontrasting
confidence: 68%
“…On the other hand, in a wide-field study, Hirano et al found a weak negative correlation for selected sectors of the choroid. Nadeem did not find such a correlation in a large group of children [ 22 ]. Our analysis differed from most previous studies as it applied both multifactor statistical modeling (age and gender adjustment) and wide-field OCT testing.…”
Section: Discussionmentioning
confidence: 99%